Malaysian parents' health literacy and perceptions regarding childhood vaccination programme - Tengku Mahmood, Tengku Farah Petri; Rafik-Galea, Shameem; Mohd Kasim, Zalina; Othman, Norlijah (2017)
There appears to be a downward trend in children’s vaccination uptake among Malaysian parents as more and more parents chose not to vaccinate their children. Thus, suggesting a need to understand Malaysian parents’ perceptions and health literacy levels regarding childhood vaccination programmes through verbal communication in order to increase confidence towards childhood vaccination programmes in Malaysia. The purpose of this study is to understand how vaccinating and non-vaccinating parents’ health literacy levels and perceptions towards childhood vaccination programmes could affect the decision whether to vaccinate or not to vaccinate their children. This study uses an in-depth interview method and a discourse analytic approach to identify the key factors in determining parents concern regarding childhood vaccination programme including their health literacy levels. The paper presents findings from the study which include parents’ motivations towards childhood vaccination and the differences between a vaccinating parent and a non-vaccinating parent. The paper will highlight whether health literacy levels of parents influence childhood vaccination. It will also highlight why it is important to understand parents’ concerns regarding childhood vaccination programmes in Malaysia and to improve communication regarding childhood vaccination programmes and uptake between parents and health care professionals in Malaysia.